Aeroacoustic Optimization Design of the Middle and Upper Part of Pantograph - Jing Guo; Xiao-Ming Tan; Zhi-Gang Yang; Yu-Qi Xue; Ya-Nan Shen; Hao-Wei Wang (Applied Sciences, 2022)
The pantograph is the main noise source of high-speed trains, of which the middle and upper parts of the pantograph account for about 50% of the whole noise energy. Taking CRH380BL pantograph as the basic prototype, three aerodynamic noise reduction measures of opening, slotting, and airfoil are introduced to build a new pantograph, and their aeroacoustic performances are comprehensively investigated through large eddy simulation (LES) and Ffowcs Williams–Hawkings (FW-H) equation method. The research results show that the open upper and lower arms (ULA) can reduce the downstream vorticity intensity and vortex structure scale, which in turn reduces the noise source intensity, thus reducing their radiated noise by approximately 1.1 dBA. The slotted ULA reduce the size of the rear vortex structure but increase the vorticity intensity, so it is difficult to effectively control their radiated noise. The airfoil bow head reduces the vorticity intensity and vortex structure scale behind it, and avoids periodic vortex shedding, thereby reducing its noise source intensity, thus reducing its radiated noise by about 1.2 dBA.